Supervising Model of Independent Enterprise Group (Study of Community Development of PT Badak NGL in Cipta Busana Cooperative - Hermansyah, Hermansyah; Sunaryo, Busori (Semarang State University, 2016)
This research aims to arrange an empowerment model of enterprise group through the program of Community Development in order to be independent and ready to compete, which is begun from the empirical study of the success of Cipta Busana Cooperative.. This research uses the descriptive analysis by using a case study on one enterprise supervised by PT Badak NGL that is Koperasi Cipta Busana (Kocibu). Kocibu is chosen to be the object of research due to its success to achieve the target to be the independent supervised enterprise in the fourth year. The data analysis method used in this research is the explorative analysis. Based on the research, there are some results such as that Kocibu is one of the supervised Micro, Small and Medium Enterprises of PT Badak NGL that could develop and be independent through several supporting programs. Some of key successes of Kocibu are as follows: a high commitment, a good leader, and intensive supervising programs. Besides, a good marketing system also contributes to the key of success. There are some aspects that naturally contribute to the Kocibu improvement and emerge naturally as follows: the leader figure and the high commitment from the stakeholders. While, the aspects emerged by design are: the supervising and training programs, the evaluation, the determination of rules, and the business targets. Hopefully, after this research has been conducted, the aspects appeared naturaly would be realized so early that the success of the public empowerment program will be able to increase.Â